The Implications of Multiple Interpretations of the Regional Head Term of Office on Legal Certainty in the 2024 Regional Elections - Imam Sanusi; Sarip; Elya Kusuma Dewi (PT. Caesarindo Triloka Persada, 2026)
The implementation of the 2024 Regional Head Elections in Indonesia generated constitutional and legal debates regarding the interpretation of regional head terms of office. Differences in interpreting the calculation of tenure between statutory provisions, Constitutional Court decisions, and technical electoral regulations created legal uncertainty concerning the eligibility and constitutional status of regional heads participating in the 2024 Regional Elections. This study aims to analyze the implications of multiple interpretations of regional head terms of office on legal certainty within Indonesia’s electoral system and to examine the legal harmonization required to prevent similar constitutional ambiguity in future elections. This research employed a normative legal research method using statutory, conceptual, and case approaches. Primary legal materials consisted of statutory regulations, Constitutional Court decisions, and electoral regulations, while secondary legal materials included legal doctrines, books, and scientific journal articles related to constitutional law, elections, and legal certainty. The findings indicate that inconsistencies between Law Number 23 of 2014 concerning Regional Government and Law Number 10 of 2016 concerning Regional Elections, combined with differing constitutional interpretations, have created multiple interpretations regarding regional head tenure. This condition has affected democratic legitimacy, equal political rights, and legal certainty in the implementation of the 2024 Regional Elections. The study further finds that the absence of harmonized electoral regulations and clear transitional provisions contributes significantly to constitutional ambiguity within Indonesia’s electoral governance. Therefore, legal harmonization, synchronization of electoral regulations, clearer legislative drafting, and stronger institutional coordination among electoral institutions are necessary to ensure constitutional certainty and democratic legitimacy in future regional elections.